Watershed Responses to Various Conservation Measures in Doon Valley - Sastry, G.; Kumar, Pramod (Journal of Soil and Water Conservation, 2022)
Event based hydrographs collected from 100 m x20 m monoclonal runoff plots on 8% slope indicate that bench terracing treatment with zero rainwater impounding produced the least runoff and soil loss. Although the runoff from graded bunding, vegetative barrier and combination treatments vary from 2.2'2.6 mm to 267.4 mm, soil loss was the lowest from vegetative barrier treatment. This is attributed to considerable reduction in overland flow velocities inducing deposition of soil behind the vegetative barriers. Analysis of watershed lag times indicate that the bench terracing has the maximum watershed lag time of .1 4.8 min. followed by vegetative barrier (9.1 min.), indicating that vegetative barriers are next best to bench terracing and superior to graded bunding and combination treatment which registered 3.1 and 6.5 minute respectively. The maize crop yields are observed to be at par under combination and vegetative barrier treatment (3316-3393 kg/ha), although graded bundling registered marginal increase in crop yields (3507 kg/ha).